2017
DOI: 10.1016/j.neuron.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Cortex-wide Emergent Properties during Motor Learning

Abstract: SUMMARY Learning involves a transformation of brain-wide operation dynamics. However, our understanding of learning-related changes in macroscopic dynamics is limited. Here we monitored cortex-wide activity of the mouse brain using wide-field calcium imaging while the mouse learned a motor task over weeks. Over learning, the sequential activity across cortical modules became temporally more compressed and its trial-by-trial variability decreased. Moreover, a new flow of activity emerged during learning, origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
284
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(325 citation statements)
references
References 45 publications
28
284
1
1
Order By: Relevance
“…Several studies recently addressed the contamination of the blood volume changes on fluorescence signal of calcium indicators like GCaMP (see, for instance, (Ma et al, 2016a;Ma et al, 2016b;Makino et al, 2017;Murphy et al, 2018;Wright et al, 2017)). The recent paper by Ma et al (Ma et al, 2016b) showed that the hemodynamic contribution is slower than the GCaMP6f signal, with an average temporal delay of 0.86 ± 0.05 s (representing the phase shift between neural activity and total hemoglobin concentration).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies recently addressed the contamination of the blood volume changes on fluorescence signal of calcium indicators like GCaMP (see, for instance, (Ma et al, 2016a;Ma et al, 2016b;Makino et al, 2017;Murphy et al, 2018;Wright et al, 2017)). The recent paper by Ma et al (Ma et al, 2016b) showed that the hemodynamic contribution is slower than the GCaMP6f signal, with an average temporal delay of 0.86 ± 0.05 s (representing the phase shift between neural activity and total hemoglobin concentration).…”
Section: Discussionmentioning
confidence: 99%
“…8) even though the activation threshold was expected to be greater. In fact, it is possible that inhibitory neurons were displaying the unexpected preference [77]. Future studies should investigate the stimulation thresholds (i.e.…”
Section: Biophysics Of the Interaction Of Polarity And Asymmetry On Nmentioning
confidence: 99%
“…In order to investigate how causal control over external objects is effected and encoded in mammalian cortex, we trained mice to control a visual feedback cursor using real-time calcium signals recorded with wide-field imaging (largely reflecting the summed spiking activity of local cells (Makino et al, 2017;Clancy et al, 2019).…”
Section: Goal-directed Control Of a Visual Cursor Using Areal Signalsmentioning
confidence: 99%